Seeking or ignoring ethical certifications in consumer choice - Dianna R. Amasino; Suzanne Oosterwijk; Nicolette J. Sullivan; Joël J. van der Weele (Tinbergen Institute, 2024)
Consumers often encounter, and claim to care about, ethical information concerning the products they purchase. Across three studies, we investigate how the accessibility of this information impacts choice. When consumers must seek out product attribute information, the impact of ethical certifications (Fairtrade and Organic) is diminished relative to other attributes. Both positive and negative framing of certifications increase their impact on choice relative to neutral frames, with negative frames having the strongest effect. However, in contrast to theories of information demand that would predict more willful ignorance of negatively framed content, negative framing has the same impact regardless of information accessibility. Together, our findings suggest that having to seek ethical certification information leads to a small reduction in the use of certifications to guide choice, but that affective framing has a larger impact on the weight placed on certifications in consumer choices regardless of the accessibility of information.
Keywords: 330; Consumer-choice; information-avoidance; information-seeking; willful ignorance; sustainability; certifications